Analysis of Students’ Misconception Using Four Tier Diagnostic Test on Fluid Topics - Dadi Rusdiana, Muslim, Oka Saputra, Agus Setiawan (International Journal of Advanced Science and Technology, 2020)
This study aims to determine the reliability and validity of the test developed and see the level of students’ misconceptions on fluid material using the four tier diagnostic test instrument. The study was conducted at SMA Negeri 2 Pagimana with a purposive sampling technique with the consideration of the highest average class learning outcomes, namely X class MIA 1. The method used in this study used a descriptive analysis design with data collection techniques through written tests. Test given to three validators has been assessed by the validator, and the problem is categorized as validThe results of this study indicate the reliability of the questions can use the Cronbach’s Alpha coefficient and obtained the reliability of the questions is 0.79. This shows that the questions used in the research are reliable. The results of the study identifying students’ misconceptions on fluid material, it can be concluded that there are still many students experiencing misconceptions with an average of 37.14% on the main topic of hydrostatic law, 46.00% on the topic of Pascal law, 65.50 on the topic of Archimedes law. 56.00% on the topic of debits and continuity and 52.00% on the topic of the Bernoulli principle. Keywords: Misconception, Fluid, Four Tier Diagnostic Tests